Clinical and physiopathological aspects of the glossopharyngeal neuralgia - Souza, Victor; Passerini, Maria; Sobral, Bianca; Baiardi, Vinicius; Junior, Hilton (Headache Medicine, 2021)
IntroductionGlossopharyngeal neuralgia is a rare syndrome characterized by paroxysms of unilateral and severe stabbing pain occurring in the nerve’s distribution. Although other neuralgias are well described in the medical literature, glossopharyngeal neuralgia and its physiopathology are not. The vascular compression at the nerve root entry zone is the primary explanation for the disease. The first-line treatment is pharmacological, including carbamazepine, oxcarbazepine, and gabapentin. Surgical treatment is offered to medication-refractory patients, and microvascular decompression surgery has the best outcomes.ObjectiveTo investigate the pathophysiological and clinical aspects of the different presentations of glossopharyngeal neuralgia.Method:A systematic review of the literature including case reports and clinical trials, was done.ResultsA search of the literature yielded 31 papers that regarded glossopharyngeal neuralgia or its variants. Eight of these reports regarded vagoglossopharyngeal neuralgia. Seven regarded the glossopharyngeal neuralgia followed by or caused by another disease.ConclusionGlossopharyngeal neuralgia is a rare disease and requires further studies on its mechanism and clinical assessment; the physician needs to know how to distinguish it from its variants and underlying causes.